The relationship between balance confidence and control in individuals with Parkinson's disease. (May 2016) - Lee, Hyo Keun; Altmann, Lori J.P.; McFarland, Nikolaus; Hass, Chris J.
Abstract: Introduction: A broad range of subjective and objective assessments have been used to assess balance confidence and balance control in persons with Parkinson's disease (PD). However, little is known about the relationship between self-perceived balance confidence and actual balance control in PD. The purpose of this investigation was to determine the relationship between self-perceived balance confidence and objectively measured static/dynamic balance control abilities. Methods: Forty-four individuals with PD participated in the study. Patients were stratified into 2 groups based on the modified Hoehn and Yahr (H&Y) disability score: early stage, H&Y ≤ 2.0 and moderate stage, H&Y ≥ 2.5. All participants completed the activities-specific balance confidence (ABC) scale and performed standing balance and gait initiation tasks to assess static and dynamic balance control. The center of pressure (COP) sway (CE95%Sway) during static balance and the peak distance between the projections of the COP and the center of mass (COM) in the transverse plane (COPCOM) during gait initiation were calculated. Pearson correlation analyses were conducted relating the ABC score and CE95%Sway and COPCOM. Results: For early stage PD, there was a moderate correlation between ABC score and CE95%Sway ( r  = −0.56, R 2  = 0.32, p  = 0.002), while no significant correlation was found between ABC score and COPCOM ( r  = −0.24, R 2  = 0.06, p  = 0.227). For moderate stage PD, there was a moderate correlation between ABC score and COPCOM ( r  = 0.49, R 2  = 0.24, p  = 0.044), while no correlation was found between ABC score and CE95%Sway ( r  = −0.19, R 2  = 0.04, p  = 0.478). Conclusion: Individuals with different disease severities showed different relationships between balance confidence and actual static/dynamic balance control. Highlights: We explored the relationship between balance confidence and control in individuals with PD. Balance confidence correlates with static balance in early stage PD. Balance confidence correlates with dynamic balance in moderate stage PD. The relationships between balance confidence and control in PD were different between early vs. moderate stage PD.